Between empires : Brazilian sugar in the early Atlantic economy, 1550-1630 - Ebert, Christopher (Atlantic world (Leiden, Netherlands), 2008)
This study examines the wholesale trade in sugar from Brazil to markets in Europe. The author finds that, in spite of the political obstacles that existed during the years covered, the trade persisted because it was not subject to monopolies and was relatively lightly regulated and taxed.